Punctuation in Early Modern English Scientific Writing: The Case of Two Scientific Text Types in Gul, Ms Hunter 135 - Barranco, Jesús Romero (Studia Anglica Posnaniensia, 2019)
Among the different topics studied by palaeography, punctuation has traditionally been disregarded by scholars for being considered arbitrary and unsystematic (Salmon 1988: 285). However, some studies carried out over the last few decades have demonstrated that the English punctuation system underwent a process of standardisation which started in the Middle English period, from a purely rhetorical to a grammatical function. Moreover, it was towards the sixteenth century when a set of punctuation marks was introduced (i.e. the semicolon), a fact that restricted the functions of major punctuation marks up to that time, such as the period and the comma (Salmon 1999: 40). The present paper analyses the punctuation system in Glasgow University Library, MS Hunter 135 (ff. 34r–121v), a volume that is most suitable for such a study as it contains two different text types belonging to the genre of medical writing: a surgical treatise and a collection of medical recipes. The results confirm that the different punctuation marks are unevenly distributed in the texts under study and, more importantly, their main functions are found at different levels within the text.